(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
The intersection of digital innovation and environmental protection is giving rise to a new paradigm—green digital transformation. This approach leverages artificial intelligence (AI), the Internet of Things (IoT), and big data analytics to promote sustainable development, optimize resource use, and monitor environmental conditions in real-time. As global environmental concerns escalate, digital tools are becoming indispensable in accelerating the green economy.